TOP DOG & POMPOM - Pitts , Sorrel (Penguin Random House UK - Ladybird, 2016)
"Top Dog and Pompom" is a story in the Ladybird Readers series. It follows the adventures of Top Dog, a playful and friendly dog, and Pompom, his fluffy companion. Together, they navigate fun and engaging scenarios that teach young readers simple lessons about friendship and teamwork.